Individual Repeatability in Marine Migratory Behavior: A Multi-Population Assessment of Anadromous Brown Trout Tracked Through Consecutive Feeding Migrations - Eldøy, Sindre H.; Bordeleau, Xavier; Crossin, Glenn T.; Davidsen, Jan G. (Frontiers in Ecology and Evolution, 2019)
Individual repeatability is a common phenomenon in behavioural ecology. Behavioural data from 38 anadromous brown trout (Salmo trutta), tracked by acoustic telemetry in 2 – 3 consecutive marine feeding migrations in two Norwegian fjord systems, were analysed for intra-individual repeatability in key aspects of their marine migration. Individual brown trout displayed significant inter-annual consistency in marine area use and in the timing of marine exit (i.e. when they returned to spawning rivers), but not in the timing of marine entry or the time spent in the marine environment each year. Intra-individual repeatability linked to changing environmental conditions should therefore be a focus for future studies, as our study raises new questions about how anadromous brown trout respond to changing conditions and anthropogenic factors in the marine environment.